Jiří Černý. [Dějiny Lingvistiky] Historia de la Lingüística. [Editorial Votobia] Universidad de Extremadura, [1996] 1998 - Estudillo Díaz, Luis Manuel (The Grove - Working Papers on English Studies, 2025)
—